2019
DOI: 10.1101/822932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In planta bacterial multi-omics analysis illuminates regulatory principles underlying plant-pathogen interactions

Abstract: Understanding how gene expression is regulated in plant pathogens is crucial for pest control 20 and thus global food security. An integrated understanding of bacterial gene regulation in the host is dependent on multi-omic datasets, but these are largely lacking. Here, we simultaneously characterized the transcriptome and proteome of a foliar bacterial pathogen, Pseudomonas syringae, in Arabidopsis thaliana and identified a number of bacterial processes influenced by plant immunity at the mRNA and the protein… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Although the signals are poorly understood, there is compelling evidence that TTSS activation occurs upon contact with target cells (13,14) and that the hrp/hrc gene cluster is controlled by multiple physiological and environmental factors that are replicated by minimal medium (15). We therefore anticipated the significant induction of hrp/hrc genes in Pto, as reported previously (15,72,73). We also observed the same phenomenon in Psa3, whereas the hrp/hrc genes in Psa1 were induced weakly and those in Psa2 were not induced at all.…”
Section: Genomic Analysis Reveals New Features Of the Ttss-related Pamentioning
confidence: 77%
“…Although the signals are poorly understood, there is compelling evidence that TTSS activation occurs upon contact with target cells (13,14) and that the hrp/hrc gene cluster is controlled by multiple physiological and environmental factors that are replicated by minimal medium (15). We therefore anticipated the significant induction of hrp/hrc genes in Pto, as reported previously (15,72,73). We also observed the same phenomenon in Psa3, whereas the hrp/hrc genes in Psa1 were induced weakly and those in Psa2 were not induced at all.…”
Section: Genomic Analysis Reveals New Features Of the Ttss-related Pamentioning
confidence: 77%
“…In this case, a gain-of-function assay is a complementary, albeit also limited, approach. For instance, we previously showed that in planta bacterial transcriptome data can predict bacterial genes that contribute to bacterial growth in planta when overexpressed (Nobori et al, 2018(Nobori et al, , 2019) . It will be necessary, in the future, to rigorously validate the biological relevance of bacterial transcriptional regulation in plants at the mechanistic level.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, a gain-of-function assay is a complementary, albeit also limited, approach. For instance, in planta bacterial transcriptome data could predict bacterial genes that contribute to bacterial growth in planta when overexpressed ( 16, 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants respond rapidly to colonization by microbes, activating innate defence strategies, which can broadly be categorized into pattern-triggered immunity (PTI) activated by microbe-associated molecular patterns (MAMPs) and effector-triggered immunity (ETI) induced upon recognition of virulence factors or their actions (Couto D. & Zipfel, 2016, Dodds & Rathjen, 2010). Virulence of Pto DC3000 largely depends on the Type-III secretion system and its secreted effectors (Kvitko et al , 2009, Nobori et al , 2018, Nobori et al , 2019, Nomura et al , 2006). A number of Type-III secreted effectors from Pto DC3000 and their in planta targets have been identified, many involved in immune suppression and some with roles in gaining access to nutrients (Wei et al , 2018, Xin et al , 2018).…”
Section: Introductionmentioning
confidence: 99%